The Relationship between Social and Sleep Quality in Adolescents at SMK Negeri 2 Binjai in 2022: The Relationship between Social Media Use and Sleep Quality in Adolescents at SMK Negeri 2 Binjai in 2022 - Margaret, Ticha; Ginting, Agustaria; Siallagan, Ance (International Journal on Health and Medical Sciences, 2024)
Social media is a facility provided for users, especially teenagers, to share information, be creative, and find new friends through Instagram, Facebook, Twitter. The use of social media for too long results in decreased sensitivity such as decreased levels of sympathy and empathy for the real world and also has an impact on sleep quality. The inability of adolescents in time management of using social media properly when at school or at home will have an impact on irregular rest and sleep patterns in adolescents. Poor sleep quality has an impact on memory decline, difficulty concentrating, causing serious health problems. Good sleep quality is seen from the depth of sleep such as the length of sleep, the time it takes to fall asleep, the frequency of awakening. Good quality sleep can be used to maintain mental, emotional balance, health, and reduce stress. This study aims to identify the relationship between social media use and sleep quality in adolescents at SMK Negeri 2 Binjai in 2022. This study uses analytical observational with a cross-sectional approach to 79 adolescents at SMK Negeri 2 Binjai. The population of 225 people where a sample of 79 teenagers is taken using a random sampling technique. The results of the study found that the use of social media was in the active category (77.2%) and sleep quality was in the poor category (60.8%). The results of the chi square test statistically found the value of p = 0.001 (p <0.05), meaning that there is a relationship between the use of social media and sleep quality in adolescents at SMK Negeri 2 Binjai.